(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Antibiotics have revolutionised medicine, helping to reduce infection-related deaths and increase life expectancy globally. They have enabled life-prolonging medical procedures and the foundation for advancements in medicine. This review explores the historical significance of antibiotics in healthcare, underscores the challenges of antibiotic resistance, and emphasises the importance of responsible antibiotic usage. It advocates for developing new antibiotics to combat resistant bacteria and ensure the continued effectiveness of antibiotic therapy in healthcare. A comprehensive search was conducted using academic databases like PubMed, Google Scholar, Web of Science, Science Direct and other search engines. The results were refined using filters, advanced search options, and relevant articles retrieved from the search. Antibiotics target and destroy bacterial cells, and each antibiotic type functions differently. However, the overuse and misuse of antibiotics, along with reduced economic incentives and challenging regulatory requirements, have resulted in antibiotic-resistant bacteria emerging, which is a cause for concern worldwide. The rapid emergence of antibiotic-resistant bacteria endangers the effectiveness of antibiotics that have saved millions of lives and transformed medicine. Antibiotics are essential in medicine, but resistance is a growing concern. New antibiotics need to be developed, and using them wisely is key to maintaining their effectiveness and positive impact on healthcare.